Formulation and characterisation of solid lipid nanoparticle hydrogels of naproxen (International Journal of Research in Pharmaceutical Sciences and Technology, 2024)
Naproxen is Non-steroidal anti-inflammatory drug (NSAID) and is considered to be first line drug in treatment of rheumatoid arthritis, osteo arthritis and ankylosing spondylitis. Naproxen undergoes first pass metabolism when taken orally and it also produces some GI problems. The aim of the study is to improve the efficacy, drug loading capacity and biocompatibility of drug by formulating in solid lipid nanoparticles. To minimize the toxicity and increase the stability of drug by encapsulating in nanoparticulate system. To optimize the developed solid lipid nanoparticle formulations. Drug Naproxen has been loaded with lipid carriers and then formulated in to Hydrogels with the objective of prolonging its action and avoiding its most side effects by incorporation of solid lipid carriers which is achieved by Nanostructured lipid carrier (NLC). Nanostructured lipid carrier was prepared by Ultra sonication or High-Speed Homogenization method.  Characterization of nanostructured lipid carrier was performed by measuring particle size, drug entrapment efficiency and in-vitro drug release. Spherical uniform particles (size below 500 nm), Drug entrapment efficiency was found to be in the range of about 69-86%. The drug release profile of all the formulations after 24 h study was found to be in the range of 43%- 94%. Formulation showing sustained release profile at the end of the study was found to be the best formulation. Optimized formulation was converted in to hydrogel with Carbopol as gelling agent was formulated and characterized for its physical appearance, pH, viscosity, spreadability, homogeneity studies. The result concludes that Naproxen loaded nanostructured lipid carrier could be a potential drug delivery system.
Keywords: Naproxen; Solid lipid nanoparticles; Bioavailability; Span 80; Tween 80